PENGARUH SENAM ASIA AFRIKA TERHADAP TINGKAT KEBUGARAN JASMANI SISWA - Schif, Nancy Trisari; Hasmarita, Sony; Sulistiadinata, Heru (Jurnal Olahraga, 2019)
The purpose of this study is to find answers to the problems that arise in this study, is there an influence of Asian-African Gymnastics on Students' Physical Fitness Levels. The object of research is the fourth grade students of the State Elementary School 079 Kopo Pajagalan Bandung Academic Year 2018/2019. And how much contribution Gymnastics Asian-African Gymnastics towards the Level of Physical Fitness Students. This study used an experimental method using a one-group pretest-posttest design research model, with data collection techniques for pretest and posttest, normality of data and independent sample t-test (free samples). As for testing data using the SPSS 25.0 program. The results showed that the Asian-African Gymnastics could affect the level of physical fitness of  fourth grade students at SD Negeri 079 Kopo Pajagalan Bandung. It can be seen from the average score of students' balking test, which initially increased by 45.68 to 49.29, which means an increase of 4.39. Another thing that strengthens is the Sig. (2-tailed) value of 0,000 <0.05, then according to the basis of decision making in the Independent Samples T-Test Test, it can be concluded that Ho is rejected and H? is accepted, which means that the results of Asian African gymnastics exercises there is an influence on improving physical fitness of students